THE RIO MAGNO UNIT (ALPINE CORSICA): A REVIEW OF ITS STRUCTURAL, STRATIGRAPHICAL AND GEOCHEMICAL FEATURES AND THEIR GEODYNAMIC IMPLICATIONS - Padoa, Elisa; Saccani, Emilio; Durand-Delga, Michel (Ofioliti, 2002)
The Rio Magno Unit (eastern Corsica) represents an Apenninic-type ophiolitic unit, quite similar to the Internal Ligurides; its ophiolitic sequence includes N-MORB basalts, Lower Cretaceous Palombini-bearing limestones, and mid Cretaceous flysch, and it is not affected by HP-LT alpine metamorphism. These features further support the hypothesis of close geodynamic relationships between the Corsican and Northern Apenninic ophiolites. We suggest that, in the Jurassic Piedmont-Ligurian oceanic basin, the Rio Magno and Internal Ligurides ophiolitic sequences represent a continuous, internal, oceanic paleo-domain. Subsequently, during the Late Cretaceous-Late Eocene, they underwent a similar orogenic evolution, escaping deep involvement during the subduction beneath the European continental margin.